1998
DOI: 10.1159/000014072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Chemical Coupling of Cerebral Blood Flow Is Compatible with Intact Neurological Outcome in Neonates with Perinatal Risk Factors

Abstract: Early detection of pathophysiological factors associated with permanent brain damage is a major issue in neonatal medicine. The aim of our study was to evaluate the significance of the CO2 reactivity of cerebral blood flow (CBF) in neonates with perinatal risk factors. Fourteen ventilated neonates with perinatal risk factors (pathological cardiotocogramm, low cord pH, postpartal encephalopathy) were enrolled into this prospective study. The study was performed 18–123 h after birth. CBF was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Our data agree with existing neonate data in the literature, 43,[73][74][75][76] but generally, these other studies measuring CO 2 reactivity were performed on other sick neonates with various clinical conditions, since it is ethically difficult to justify the use of methods requiring contrast agents or anesthesia to measure local CBF and also the artificial induction of hypercapnia. Thus, we are unable to compare our data to the responses of healthy neonates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data agree with existing neonate data in the literature, 43,[73][74][75][76] but generally, these other studies measuring CO 2 reactivity were performed on other sick neonates with various clinical conditions, since it is ethically difficult to justify the use of methods requiring contrast agents or anesthesia to measure local CBF and also the artificial induction of hypercapnia. Thus, we are unable to compare our data to the responses of healthy neonates.…”
Section: Discussionsupporting
confidence: 90%
“…43,[73][74][75][76] Vascular reactivity to CO 2 was not found to depend on baseline CBF ASL-MRI or baseline PaCO 2 ͑p = 0.1 for both͒. The NIRS data was also in good agreement with previous NIRS studies on hypercapnia-induced changes in neonates.…”
Section: -62supporting
confidence: 86%
“…The 133 Xenon inhalation is considered the gold standard method for CBF measurement [19,20] . The total CBF in neonates at term measured using 133 Xe method is in the range of 20-55 ml/100 g/min [19,21,22] . We found an overall mean total CBF of 104 ml/min, which is consistent with reported data assuming an average brain weight of 300 g [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In infants with birth asphyxia, hyperperfusion is thought to be a sign of permanent brain damage with poor neurodevelopmental prognosis. The reason for this cerebral hyperaemia and low RI is thought to be severe vasoparalysis, a form of irreversible cerebral vascular injury (12,16,17). The severity of vasoparalysis and cerebral hyperaemia is thought to correlate with the degree of brain injury and presumably the severity of the asphyxial insult (12,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported high cerebral blood-flow (CBF) velocities and significantly lowered resistance indices (RI) in infants with severe hypoxicischaemic encephalopathy (HIE) at the age of 24-72 h (11)(12)(13)(14)(15). In infants with birth asphyxia, delayed hyperperfusion is thought to be a sign of permanent brain damage with poor neurodevelopmental outcome (12,16,17).…”
mentioning
confidence: 99%